Pembelajaran Berdiferensiasi Produk Dalam Modul Ajar Teks Proposal Kegiatan Kelas XI SMA - Arda Sedyoko; Siti Latifah Mubasiroh (Jurnal Sadewa : Publikasi Ilmu Pendidikan, pembelajaran dan Ilmu Sosial, 2023)
The new paradigm change in the world of education in Indonesia requires teachers to be able to implement a learning model that is able to be oriented towards the characteristics of students. One learning model that can be used to accommodate the diversity of student characteristics is differentiated learning. Thus, this article aims to describe the development of differentiated learning in the aspect of product differentiation. The development of product differentiation learning is implemented in the activity proposal text teaching module for class XI SMA. This research uses the method literature review (literature review). This research presents search results regarding articles related to the topic of differentiated learning. Relevant articles are then reviewed and synthesized in such a way that they can provide information in the form of a more meaningful presentation. Based on the results of the studies, synthesis and exploration that have been carried out, it can be understood that each student has different talents and interests. Product differentiation is intended so that students are able to process according to their talents and interests. Apart from that, the results of the study of differentiated teaching modules for learning proposal text activities that have been developed show that learning to write proposal texts can be said to implement a differentiated learning model from the product aspect.